2010
DOI: 10.1186/1752-0509-4-163
|View full text |Cite
|
Sign up to set email alerts
|

Integrated analysis of mutations, miRNA and mRNA expression in glioblastoma

Abstract: BackgroundGlioblastoma arises from complex interactions between a variety of genetic alterations and environmental perturbations. Little attention has been paid to understanding how genetic variations, altered gene expression and microRNA (miRNA) expression are integrated into networks which act together to alter regulation and finally lead to the emergence of complex phenotypes and glioblastoma.ResultsWe identified association of somatic mutations in 14 genes with glioblastoma, of which 8 genes are newly iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
86
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(90 citation statements)
references
References 65 publications
3
86
0
1
Order By: Relevance
“…Seven proteins (ANXA2, XRCC6, SCARB2, GOLIM4, CAMKIIA, RAB3A, and SV2A) were thus selected, and IHC was performed with six individual cases. Comparison with the primary transcriptome data published by TCGA Network supports altered expression of these proteins (6). Other differentially expressed proteins such as atlastin 3 (ATL3), paralemmin 2 (PALM2), and neuronal growth regulator 1 (NEGR1), which have important biological functions, were examined by Western blots because of nonavailability of the IHC-compatible antibodies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seven proteins (ANXA2, XRCC6, SCARB2, GOLIM4, CAMKIIA, RAB3A, and SV2A) were thus selected, and IHC was performed with six individual cases. Comparison with the primary transcriptome data published by TCGA Network supports altered expression of these proteins (6). Other differentially expressed proteins such as atlastin 3 (ATL3), paralemmin 2 (PALM2), and neuronal growth regulator 1 (NEGR1), which have important biological functions, were examined by Western blots because of nonavailability of the IHC-compatible antibodies.…”
Section: Resultsmentioning
confidence: 99%
“…They also showed a positive association with markers of stem-like cells, including CD133 and nestin (4). In a large scale analysis of GBM by The Cancer Genome Atlas (TCGA) Network, a total of 601 genes was sequenced for detection of somatic mutations, and expression of over 12,000 genes was measured in more than 200 GBM cases to understand altered genes and pathways on the basis of copy number variations, mutation frequency analyses or differentially expressed transcripts including miRNAs (5,6). Analysis based on TCGA transcriptome data revealed that GBMs could be subtyped into four different groups, each defined by a signature of 210 transcripts (7).…”
mentioning
confidence: 99%
“…Furthermore, we assessed the effects of miR-7 mimic transfection on the protein levels of all the above oncogenes and several accompanying downstream genes (23)(24)(25)(26)(27)(28)(29)(30). Western blotting showed that expression of PI3K and Raf-1 was downregulated in TJ899 cells in a dose-dependent manner after 3 days of miR-7 mimic transfection.…”
Section: Mir-7 Inhibits Gbm Malignancymentioning
confidence: 99%
“…The Cancer Genome Atlas (TCGA) generated large-scale multi-dimensional datasets to catalogue cancer alterations. GBM is the first cancer studied by TCGA (5).…”
Section: Introductionmentioning
confidence: 99%